2022
DOI: 10.3390/ijpb13010003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Secondary Metabolites from Plant Sources: Types, Synthesis, and Their Therapeutic Uses

Abstract: Plants are the source of various photochemicals; metabolites are used in medicinal and environmental sectors as well as being widely used in commercial and pharmaceutical products. Although they produce a number of medicinal products, either already on the market or under trial, the amounts obtained from plant sources are very minute or difficult to synthesize at an industrial level due to the complex chemical composition and chirality exhibited by these compounds. However, plant cell cultures offer a good alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(103 citation statements)
references
References 80 publications
1
67
0
Order By: Relevance
“…They are of several classes, such as phenolic compounds, alkaloids, or terpenes, and are rising to prominence in several fields. 9 Hemp seed phenolic compounds belong essentially to the phenylpropionamides class comprising phenylanamides and lignanamides. 10 Hemp seeds are particularly rich in caffeoyltyramine, cannabisin A, and cannabisin B molecules.…”
Section: Introductionmentioning
confidence: 99%
“…They are of several classes, such as phenolic compounds, alkaloids, or terpenes, and are rising to prominence in several fields. 9 Hemp seed phenolic compounds belong essentially to the phenylpropionamides class comprising phenylanamides and lignanamides. 10 Hemp seeds are particularly rich in caffeoyltyramine, cannabisin A, and cannabisin B molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of reports on the safety, efficacy and use of synthetic drugs remain a matter of debate in the medical community, naturally occurring bioactive molecules of plant origin still play a dominant role in the treatment of ailments due to their high tolerance and acceptance by patients during treatment. The use of typical synthetic drugs in chemotherapy is associated with serious side effects such as decreased appetite, hair loss, gastrointestinal changes, neurological dysfunction, and drug resistance, which weaken the patient and reduce the quality of life, both mentally and physically [ 16 , 24 , 26 , 28 , 30 , 31 , 32 , 33 ]. Studies have shown phytochemicals to be less toxic and more effective, in some regards.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites have numerous functions in plants, including plant growth and development processes, innate immunity, defense response signaling, and response to environmental stresses [83] as well as root microbiomes [84] (Figure 11). Secondary metabolites can also be used as food additives, pharmaceuticals, and cosmetics ingredients [85]. Enormous plants, mainly medicinal plants, that can produce bioactive secondary metabolites include Chinese medicinal herbs, as reported by El-Ramady et al [86] and in Tables 2 and 3.…”
Section: Medicinal Plants and Their Bioactive Compoundsmentioning
confidence: 96%
“…Recently, a great concern for plant bioactives and therapeutic agents has been reported in the literature (e.g. [81,85,115]), as reported in Table 3.…”
Section: Medicinal Plants and Their Bioactive Compoundsmentioning
confidence: 99%